Architects’ practices of the integration of construction worker’s safety features : a survey / Farhan Md Dahlan ... [et al.] - Md Dahlan, Farhan; Yusop, Norhafizah; Abu Bakar, Norbaizura; Mat Isa, Siti Sarah (2012)
The construction industry is known to have some of the most hazardous activities in any country development. The hazards exposed to construction workers on site often place the contractor as the one to blame. Architects as the leader in the design team can play an effective role in minimizing the hazards. However, there is yet to be research that focuses on the architects‟ roles in hazard mitigation. This study investigates the possibility of integrating the construction workers‟ safety features into building designs in the Malaysian construction industry. The result could assist the clients in reducing related costs due to injuries and death on the construction site. A survey on the architecture consultant firms in Klang Valley Malaysia has found that the respondents do integrate construction workers‟ safety in their designs, yet the integration is insignificant because it is done through their own initiatives and on an informal basis. In addition, the integration is only considered during the third phase of the design review. The findings further indicate that certain designs have been taken into consideration such as providing warning and information about site conditions, designing and scheduling railings as part of the erection process, designing window sills and parapet wall 42 inches above the floor, designing permanent guardrails around skylights and providing warning in the plans and specification construction of floor openings during construction. The findings may be able to provide some new insights on the architect‟s involvement in integrating construction workers‟ safety features during the design process. Promoting and improving the integration of construction workers‟ safety features would be more promising to improve construction site hazards.